Edible bird’s nest attenuates procoagulation effects of high-fat diet in rats - Yida Z; Imam MU; Ismail M; Ismail N; Hou ZP (Dove Medical Press, 2015)
Zhang Yida,1,2 Mustapha Umar Imam,1 Maznah Ismail,1,3 Norsharina Ismail,1 Zhiping Hou1 1Laboratory of Molecular Biomedicine, Institute of Bioscience, Universiti Putra Malaysia, Serdang, Selangor, Malaysia; 2Cardiology Department, Affiliated Hospital of Chengde Medical University, Chengde, Hebei, People’s Republic of China; 3Faculty of Medicine and Health Sciences, Department of Nutrition and Dietetics, Universiti Putra Malaysia, Serdang, Selangor, Malaysia Abstract: Edible bird’s nest (EBN) is popular in Asia, and has long been used traditionally as a supplement. There are, however, limited evidence-based studies on its efficacy. EBN has been reported to improve dyslipidemia, which is closely linked to hypercoagulation states. In the present study, the effects of EBN on high-fat diet- (HFD-) induced coagulation in rats were evaluated. Rats were fed for 12 weeks with HFD alone or in combination with simvastatin or EBN. Food intake was estimated, and weight measurements were made during the experimental period. After sacrifice, serum oxidized low-density lipoprotein (oxLDL), adiponectin, leptin, von willibrand factor, prostacyclin, thromboxane and lipid profile, and whole blood coagulation indices (bleeding time, prothrombin time, activated partial thromboplastin time, red blood count count, and platelet count) were estimated. Furthermore, hepatic expression of coagulation-related genes was evaluated using multiplex polymerase chain reaction. The results indicated that EBN could attenuate HFD-induced hypercholesterolemia and coagulation similar to simvastatin, partly through transcriptional regulation of coagulation-related genes. The results suggested that EBN has the potential for lowering the risk of cardiovascular disease-related hypercoagulation due to hypercholesterolemia. Keywords: edible bird’s nest, coagulation, high-fat diet, hypercholesterolemia, nutrigenomics